(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Background: Neutrophil to lymphocyte ratio has emerged as potential biomarker for cancer prognosis due to its accessibility and ease of calculation using routine blood- cell counts. Patients of non-small cell lung cancer (NSCLC) with higher neutrophil to lymphocyte ratio (NLR) before treatment have worse prognosis than those patients who have lower neutrophil to lymphocyte ratio (NLR). The objective of this study is to evaluate the prognostic role of neutrophil to lymphocyte ratio (NLR) in stage IV non-small cell lung cancer. Patients and methods: This prospective cohort study was conducted from 8th January to 8th July 2023 in the indoor Pulmonology Department at KEMU, Lahore, in collaboration with the Oncology Department. A total of 114 biopsy-confirmed, treatment-naïve stage IV NSCLC patients aged 40–80 years were enrolled using non-probability consecutive sampling. Patients with prior treatment or active infections were excluded. Study parameters included age, gender, baseline NLR (≤3.5 or ≥3.5), and survival at 6 and 12 months. Data were collected using a structured proforma from patient records and laboratory reports. NLR was calculated from baseline CBC. Statistical analysis was performed using SPSS v26; independent t-tests were used to compare survival outcomes, with p<0.05 considered significant. Disease-related survival was defined as the time from diagnosis to death due to NSCLC. Results: The majority of patients were male in both groups (77.2% in NLR ≤3.5; 78.9% in NLR ≥3.5). Treatment response differed significantly: in the NLR ≤3.5 group, 59.6% had partial response, 12.3% stable disease, and 28.1% progressive disease, whereas in the NLR ≥3.5 group, 89.5% showed progressive disease. At 6 months, the relative risk (RR) of mortality for patients with NLR ≥3.5 was 2.52 compared to those with NLR ≤3.5. At 12 months, mortality was 85.7% in the NLR ≥3.5 group vs. 62.3% in the NLR ≤3.5 group, with an RR of 2.64, indicating a significantly poorer prognosis in patients with elevated NLR. Conclusion: This study underscores the prognostic value of neutrophil-to-lymphocyte ratio (NLR) in stage IV NSCLC, with elevated NLR linked to poorer survival and progressive disease. NLR could be a valuable biomarker for guiding prognosis and treatment in these patients.